Biplane Imaging Versus Standard Transverse Single-Plane Imaging for Ultrasound-Guided Peripheral Intravenous Access: A Prospective Controlled Crossover Trial - David Convissar, MD (Wolters Kluwer, 2021)
OBJECTIVES:. Obtaining peripheral IV access in critically ill patients is often challenging especially for novice providers. The availability of biplane imaging for ultrasound guided peripheral access has the potential to improve successful venous cannulation compared with standard plane imaging. DESIGN:. Single-center quasi-randomized (alternate allocation) crossover trial. SETTING:. Surgical ICU at the Massachusetts General Hospital. SUBJECTS:. Twenty surgical ICU nurses with no prior experience using ultrasound for peripheral IV were enrolled. INTERVENTIONS:. All participants viewed instructional videos on single-plane and biplane imaging for peripheral IV insertion. The participants were then quasi-randomly assigned to use either single-plane or biplane imaging for peripheral IV insertion using a phantom model. The time to catheter completion, successful lumen cannulation, and attempts in which the needle was observed to go through the back wall of the vessel were recorded for each of the three attempts. The following day the participants repeated the peripheral IV insertion with the alternate imaging modality. MEASUREMENTS AND MAIN RESULTS:. Biplane imaging compared with single-plane imaging was associated with a significantly greater overall success rate (78.3% ± 22.4% vs 41.7% ± 26%; p < 0.001), higher first-pass success rate (80% ± 41% vs 45% ± 51%; p = 0.015), faster cannulation times (27.8 ± 14.8 vs 36.6 ± 15.8 s; p = 0.003), and reduced frequency of backwall perforations (0.4 ± 0.7 vs 1.5 ± 0.8; p < 0.001). CONCLUSIONS:. This proof-of-principle study demonstrates that the biplane ultrasound imaging approach for vessel cannulation resulted in an overall faster, more successful, and safer peripheral IV access than the standard single-plane transverse approach when performed by novice ultrasound users.